If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8e + 5)(8e + -5) = 0 Reorder the terms: (5 + 8e)(8e + -5) = 0 Reorder the terms: (5 + 8e)(-5 + 8e) = 0 Multiply (5 + 8e) * (-5 + 8e) (5(-5 + 8e) + 8e * (-5 + 8e)) = 0 ((-5 * 5 + 8e * 5) + 8e * (-5 + 8e)) = 0 ((-25 + 40e) + 8e * (-5 + 8e)) = 0 (-25 + 40e + (-5 * 8e + 8e * 8e)) = 0 (-25 + 40e + (-40e + 64e2)) = 0 Combine like terms: 40e + -40e = 0 (-25 + 0 + 64e2) = 0 (-25 + 64e2) = 0 Solving -25 + 64e2 = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 64e2 = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 64e2 = 0 + 25 64e2 = 0 + 25 Combine like terms: 0 + 25 = 25 64e2 = 25 Divide each side by '64'. e2 = 0.390625 Simplifying e2 = 0.390625 Take the square root of each side: e = {-0.625, 0.625}
| 3y-4+y+18=8y+20-6y | | 9c+15c^3=0 | | 1000.00+500000x=1350.00 | | 20=13y-8y | | -84=-7(8-4K) | | 8y-12-3y=-2 | | 9x+8y=-16 | | 4(4x-3)=8(2x-2)+4 | | 9n-20=7 | | 6x-10=3x+5 | | 42y-7=31 | | 54=4w+2w | | 90×2/3 | | M^2+56=15m | | 54=4w | | x-3=-2+3 | | 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 |